Response Spectrum Analysis of a RC Building Based on Complete Quadratic Combination (CQC) Method. Issue 1 (1st October 2022) - Banerjee, Debargha; Das, Debasish; Ghosh, Uddipta; Debnath, Dina; Debnath, Santanu; Malakar, Snehasish; Das, Ratnadwipa; Datta, Sanjoy; Hossain, Syed Ealham
Abstract: In the realm of structural design, Seismic Analysis is crucial. Many structures have collapsed because of earthquakes; as a result of numerous studies, different methods for analysing and determining vibration modes of a structure have been created. Seismic analysis can be done in two ways: static analysis and dynamic analysis. The basic mode of vibration dominates the response in the static technique of seismic analysis, and the mass and stiffness of the structures are evenly distributed, resulting in a regular shape, however this assumption fails for irregular buildings. As a result, dynamic methods are used to solve this issue. Response spectrum is one such dynamic method that is relatively simple to utilize compared to others. The benefit of employing the seismic response spectrum method is that it aids in the prediction of displacement and member forces in structural systems. As a result, this method aids in determining peak structural responses within a linear range, which can then be used to calculate lateral forces created in structures due to earthquakes, allowing for more earthquake-resistant building design. Although this method is approximate, it is a cost-effective and beneficial method for preliminary design research. The response spectrum method is used on STAAD.PRO V8i software to design a G+4 residential structure in our study. The building's measurements are 16 meters long, 12 meters wide and 15 meters tall. The foundation was built to a depth of 1.5 meters. The structure was built to withstand earthquakes in seismic zone III on medium-density soil. Dead load (IS 875 Part I), Live load (IS 875 Part II), Seismic Load (IS 1893 Part I), and Wind Load are some of the load instances that were presented based on Indian Standard code (IS 875 Part III). To acquire the best response, the response spectrum modal combination Complete Quadratic Combination (CQC) is used. Various parameters like wind intensity, seismic parameters, dynamic weight, modal participation factors, base shear and peak storey shear are calculated. Base shear and peak storey shear are found to maximum in Mode 2 and between 5 th and 6 th respectively.